Navigating the Spanish-Chamorro Transoceanic Encounter: Authorship and Collaborative Work in the Boxer Codex - Serratos, Brayan (Revista Canadiense de Estudios Hispánicos, 2024)
The article aims to deepen understanding of the Boxer Codex by analyzing the author and artist of the inaugural transoceanic encounter between the Spanish and the Chamorro people, depicted in the manuscript’s initial image and detailed in the first accompanying narrative. Although most of the narratives remain anonymous, they offer valuable insights into the dynamics of knowledge exchange and cultural mediation among the diverse ethnic groups involved in the manuscript’s creation. This study not only reveals the subtle hints about the author but also illuminates the collaborative efforts of the artist and the influence of cultural intermediaries involved in its production.